The effect of relaxation therapy of dzikir prayer on dysmenorrhea pain of D3 midwifery students in Garut District - Handayani, Titi Purwitasari; Ernawati, Ernawati; Hidayat, Dian Roslan (Institute of Computer Science (IOCS), 2024)
Dysmenorrhea is a reproductive health problem that occurs in adolescents. The prevalence of dysmenorrhea in Indonesia reaches 64.25% in women aged 13-25 years. This condition not only causes physical discomfort, but can also have a significant impact on the quality of life and productivity of sufferers which can affect their quality of life and academic performance. Relaxation therapy of dhikr prayer is a potential non-pharmacological approach in pain management, but its effectiveness in dysmenorrhea still needs further research. This study aims to evaluate the effect of relaxation therapy of dhikr prayer on the intensity of dysmenorrhea pain in D3 Midwifery students in Garut Regency. Pre-experimental design with One Groups Pretest-Posttest Design approach. The sample consisted of 36 selected according to inclusion and exclusion criteria. The sampling technique used purposive sampling. One group was measured for dysmenorrhea pain assessment before and after being given dhikr prayer therapy. Measurement of pain intensity was measured using the Numeric Rating Scale (NRS) and questionnaires before and after the intervention. Results: Data analysis showed a significant decrease in pain intensity before and after zikir prayer relaxation therapy with a p-value of 0.000 (p<0.05). Zikir prayer relaxation therapy was proven effective in reducing the intensity of dysmenorrhea pain in D3 Midwifery students. These findings indicate the potential for integrating a spiritual approach in dysmenorrhea pain management and open up opportunities for further research on the effectiveness of spiritual-based interventions in midwifery practice.